Compreendendo a inovação social: as relações entre atores no contexto Living Lab - Silva, Maurício Goulart da (Universidade do Vale do Rio dos Sinos, 2019)
The objective of this work is to explore how the different actors relate in order to implement Social Innovation initiatives. For this, the Relational View (DYER; SINGH, 1998) is used as a theoretical lens, mainly based on the logic of its sources of relational rent. A unique case study was developed, having the Living Lab Habitat (Vitória/ES) as an empirical field, the only Brazilian one still accredited by the European Network of Living Labs. Fifteen people involved with Living Lab were interviewed between January and March 2018, so this material was submitted to Content Analysis. Even though coming from the economic sciences, the Relational View has the potential of being linked to Social Innovation, since, in the first one, the relationships are created for the generation of competitive advantage, in the other, there is the interaction between actors to generate collaborative advantage, in the direction of promoting social value. Three sources of relational gains have been related to the context of Social Innovation - complementarity of resources and capabilities among actors, sharing knowledge and learning routines and effective governance. As the main findings, the centrality of relations between actors was identified as being mediated by informal elements of governance, highlighting the sharing of a common purpose. Actors can be considered the main resources of the network, contributing primarily to knowledge and financing. Co-creation emerges as the element that legitimizes the propositions and implementations developed in the living lab. As managerial contributions, it should be pointed out that projects in Social Innovation tend to end as soon as the sponsorship ends, and, in the social sphere, to think about initiatives that are sustainable. Another contribution is that when actors whose knowledge is very asymmetrical between them have to work together, they may misunderstand and it generates difficulty of learning transmission and perception of the impact generated. Finally, it proposes a theoretical framework for the Relational View focused on initiatives in Social Innovation, as well as give directions to future studies in this field.
Keywords: Inovação Social; Visão Relacional; Living Lab; Colaboração; Estudo de Caso; Social Innovation; Relational View; Living Lab; Collaboration; Case Study; ACCNPQ::Ciências Sociais Aplicadas::Administração